SISTEM INFORMASI GEOGRAFIS UNTUK MENGIDENTIFIKASI KETERJANGKAUAN DAN POLA PERSEBARAN LOKASI PUSKESMAS DI KOTA BATAM - Farouki Dinda Rassarandi; Adelia Adeza Rajagukguk (Prosiding Seminar Nasional Terapan Riset Inovatif (SENTRINOV), 2024)
Batam City is known as the industrial city, so the high growth of industrial activity, population, and economy in Batam City is as rapid as the spatial change, which is expected to be in line with health development. To know the affordability of puskesmas services belonging to the Government of the City of Batam relative to the availability and settlement of the population in each Batam district, use the spatial buffer and service area analysis that produces affordability. Puskesmas is able to serve 78% of the population in Batam City, and the percentage of the settlement that has affordable puskesmas services in 12 Batam Districts To find out the pattern of spread of puskesmas in the city of Batam, then use the Geographic Information System (GIS), which is the analysis of the nearest neighbors, with the result that the spread pattern is uniform or dispersed with the value T = 1.272326. Knowing the availability and patterns of spread of the location of puskesmas can provide a broad picture to the public and be an evaluation material for governments and parties that support health development, especially in the development of health facilities in the City of Batam, so that they can provide health services with the best quality.